Meta-analysis of trigger timing in normal responders undergoing GnRH antagonist ovarian hyperstimulation protocol - Qijun Xie; Danyu Ni; Sisi Chen; Wenjie Zhang; Jue Wang; Xiufeng Ling; Rong Shen (BMC, 2024)
Abstract Importance The first meta-analysis focused only on gonadotropin-releasing hormone (GnRH) antagonists, which helped determine the effect of delay trigger on pregnancy outcomes. Objective To evaluate the impact of delay trigger compared with standard trigger in normal responders undergoing GnRH antagonist protocol in improving pregnancy outcomes. Methods Studies published before April 2023 in PubMed, EMBASE, Cochrane Library, Web of Science, CNKI, Wanfang, VIP and CBM databases were searched. Randomized controlled trials (RCTs) and cohort studies conducted in normal responders reporting the efficacy of delay trigger using GnRH antagonist protocol were included. Data were combined to calculate mean differences (MD) for continuous variables and odd ratios (OR) for categorical variables with their corresponding 95% confidence intervals (CIs). Heterogeneity was assessed using Cochran's Q test. Results Endpoints, including clinical pregnancy rate (CPR), live birth rate (LBR), the number of oocyte retrievals and embryos, and fertilization rate, were analyzed. Six (6) clinical studies (4 RCTs and 2 cohort studies) with 1,360 subjects were included. The pooled results showed that the number of oocyte retrievals (MD: 1.20, 95% CI: 1.10, 1.30, p < 0.01), fertilization rate (MD: 0.64, 95% CI: 0.29, 0.99, p < 0.01) and days of stimulation (MD: 0.95; 95% CI: 0.54, 1.37; p < 0.01) in the delay trigger group was significantly higher than that in the standard trigger group. However, there was no significant difference in the number of embryos (MD: 0.19, 95% CI: -0.29, 0.67, p = 0.44), CPR (OR: 1.12; 95% CI: 0.72, 1.75; p = 0.062), and LBR (OR: 1.23; 95% CI: 0.90, 1.66; p = 0.19) between the two trigger groups. Conclusion Delaying trigger time in GnRH antagonist protocol increased the number of oocytes retrieved but not the number of embryos. Furthermore, delay trigger shot was not associated with a clinical benefit towards CPR and LBR in women who underwent fresh embryo transfer cycles. Trial registration The International Prospective Register of Systematic Reviews (PROSPERO), registration number: CRD42023413217.